The Impact of Science-Based Education on Colostrum Provision Behavior Among Postpartum Mothers: A Case Study in Aceh Province, Indonesia - Idawati Idawati; Yuliana Yuliana; Meliani Sukmadewi Harahap; Nurlaely Nurlaely (Jurnal Penelitian Pendidikan IPA, 2025)
Maternal and toddler health issues are one of the main indicators of a nation's health; one way to reduce infant mortality is to provide the best food, namely breast milk (ASI), especially colostrum. Colostrum is the first milk from a yellowish liquid produced several days after birth. This study aimed to determine the effect of science education for postpartum mothers on providing colostrum to infants in the obstetrics room of Tgk. Chik Ditiro Regional Hospital, Aceh Pidie Regency. The methodology of this study is quantitative research with an analytical research design and a cross-sectional approach. The sample of this study was 30 mothers who gave birth in the obstetrics room. The research instrument used was a questionnaire/direct interview with respondents. Data were analyzed univariately and bivariate using the chi-square test. The study's results showed a relationship between knowledge, attitudes, practices, or actions and maternal behavior in terms of providing colostrum. Science education for postpartum mothers is very important to improve mothers' understanding of the importance of colostrum for babies. Based on several previous studies, it was found that science education in the form of counseling can significantly increase the knowledge and tendency of mothers to provide colostrum to their babies after birth. The study highlights the value of targeted science-based education in maternal health literacy, supporting science education integration into community health practices